The Young Person Check: screening for sexually transmitted infections and chronic disease risk in remote Aboriginal and Torres Strait Islander youth. (30th July 2013) - Fagan, Patricia; Cannon, Fiona; Crouch, Alan
Abstract Objective : This paper describes the implementation and selected outcomes of the Young Person Check (YPC), a high‐coverage screening program in far north Queensland targeting remote youth aged 15–24 years for sexually transmissible infections (STI) and chronic disease risk. The YPC was conducted 19 times in eight discrete remote communities and one community cluster between 2009 and 2012. Methods : Narrative description of consultation processes, YPC planning, recruitment strategies, logistics, screen design, additional costs and data management; analysis of coverage by location, age group and gender, selected STI management outcomes, and clinic‐based STI testing separate from YPCs. Results : A total of 3, 686 episodes of care were delivered, including 3, 083 to Indigenous youth aged 15–24 years. Overall coverage of the 15–24 population was 73% for females and 72% for males. Median time to treatment for chlamydia/gonorrhoea cases was 13 days and 63% of cases had at least one contact treated. Clinic‐based STI testing did not decrease. Conclusions : Positive outcomes of the YPC program, including satisfactory participation, rest on a rigorous approach to planning, recruitment and implementation; provision for STI follow‐up; and data management. Implications : Testing and treatment strategies form an important element of efforts to address endemic STI and reduce HIV risk in remote Australian populations. Complementary population testing strategies will continue to be utilised and may contribute, if coverage is satisfactory. Programs such as the YPC should be considered in settings where the conditions outlined here can be met.